Detection and Genomic Characterization of Novel Mammarenavirus in European Hedgehogs, Italy - Barbara Di Martino; Federica Di Profio; Maria Teresa Capucchio; Ilaria Prandi; Serena Robetto; Giuseppe Quaranta; Giuseppina La Rosa; Elisabetta Suffredini; Fulvio Marsilio; Vito Martella; Vittorio Sarchese (Emerging Infectious Diseases)
Mammarenaviruses are noteworthy zoonotic pathogens, and the main reservoirs are rodent species. We report the detection of a novel mammarenavirus in 6/183 (3.3%) in necropsied European hedgehogs (Erinaceus europaeus) collected in Italy. The whole-genome sequence obtained for 4 strains revealed a marked genetic diversity but a monophyletic origin.